2015
DOI: 10.1007/s10047-015-0847-8
|View full text |Cite
|
Sign up to set email alerts
|

Relative permittivity measurement during the thrombus formation process using the dielectric relaxation method for various hematocrit values

Abstract: The relative permittivity ε' and the dielectric loss ε″ for various hematocrit values H for static bovine blood condition have been measured using the dielectric relaxation method to detect thrombosis in real time. The suitable measurement frequency f m ranged within 60 kHz to 1 MHz, and the relaxation frequency of red blood cells (RBCs) f rc was observed to be 2 MHz. In the f m, the temporal change of normalized ε' exhibited a minimum (called as bottom point). The bottom point was observed to be exponentially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Figure 4 displays the fibrin cube with different concentrations of MMPs (dilute and non-dilute). The outputs from Case 1 ( Table 1) Table 2 and were derived from the literature [17][18][19][20][21]. The estimation of the magnetic field and flux was followed by the estimation of Maxwell's force distribution in the MMPs as per (9) -(11).…”
Section: Case 2: Stress and Strain Estimation On Fibrin Samplementioning
confidence: 99%
“…Figure 4 displays the fibrin cube with different concentrations of MMPs (dilute and non-dilute). The outputs from Case 1 ( Table 1) Table 2 and were derived from the literature [17][18][19][20][21]. The estimation of the magnetic field and flux was followed by the estimation of Maxwell's force distribution in the MMPs as per (9) -(11).…”
Section: Case 2: Stress and Strain Estimation On Fibrin Samplementioning
confidence: 99%
“… 77 78 One study estimated the risk of thrombus formation by detecting circulating platelet derived microparticles 78 whereas another study utilised dielectric relaxation method to detect thrombosis in real time using bovine blood. 77 A recent study by Santorelli et al demonstrated that based on EIS measurements, blood clot analogues can be classified into RBC rich or platelet and fibrin rich clots. 79 This promising observation suggests EIS may be useful to detect AIS thrombus characteristics in the acute care setting, although considerable further research is needed to translate this observation to real AIS thrombi in situ and in thrombi of heterogeneous composition.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also shown that aggregation of RBCs76 influences EIS measurements. Few studies have used EIS for thrombus detection 77 78. One study estimated the risk of thrombus formation by detecting circulating platelet derived microparticles78 whereas another study utilised dielectric relaxation method to detect thrombosis in real time using bovine blood 77.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to the slow response time and qualitative nature of conventional methods, it is necessary to find faster and more accurate methods [6,7], especially for longer term use. Therefore, methods of real-time quantitative monitoring for the anticoagulation degree [8] or assessment of the blood-clotting reaction in MCS circuits [9][10][11][12][13] have been studied and developed. However, these methods are not yet suitable for practical clinical use, because they cannot be assembled where the thrombus formation actually occurs in MCS devices during actual clinical use.…”
Section: Introductionmentioning
confidence: 99%